Pemilihan pegawai akademik di IPTA melalui kaedah pembuatan keputusan pelbagai kriteria: satu kajian kes di Universiti Malaya - Khairul Anuar Mohd Ali,; Fazli Idris,; Wu , Ziou Hon (Penerbit ukm, 2008)

(untitled)
The purpose of this study is to determine the criteria and subcriteria that are being considered for the first level academic staff selection (Grade DS 45) in University of Malaya. This study also aimed to rank the criteria and subcriteria based on the weight value for each of the criteria and subcriteria. A comparison among the important criteria is done for each faculty. Questionnaires were distributed to collect the data. Rank Order Centroid technique is used to calculate the weight value for each criteria and subcriteria. The results show that academic qualification is the most important criteria (0.4030), followed by research criteria (0.2030), skill / ability (0.1511), work experience (0.1442) and personality (0.0988)